Economic justification of clinical pharmacists employment - Štuhec, Matej (Anali PAZU, 2022)
A clinical pharmacist is becoming an indispensable member of the healthcare team in many countries in all medication-related processes. These activities include admission, monitoring during treatment, discharge, and other relevant interventions. Clinical pharmacist interventions lead to lower overall treatment costs, fewer medication errors and medication-related problems, and improved quality of life. There is much evidence about economic benefits in the literature, but many healthcare systems do not follow this practice, and therefore clinical pharmacists are relatively under-employed. In the review, we will present some important research on this topic, including an overview of the current Slovenian situation and recommendations.